2016
DOI: 10.1093/aje/kwv206
|View full text |Cite
|
Sign up to set email alerts
|

Severe Human Parechovirus Infections in Infants and the Role of Older Siblings

Abstract: Human parechovirus (HPeV) is a cause of severe morbidity among infants and young children. To evaluate the associations between early environmental risk factors and HPeV infections, we carried out a nationwide cohort study linking registry data on birth and sibship characteristics with a laboratory surveillance database, covering all HPeV infections detected in Denmark during 2009-2012 among children <5 years of age. Incidence rate ratios were calculated in log-linear Poisson regression analyses. Overall, 133 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 34 publications
3
18
1
3
Order By: Relevance
“…PeV-A1 detections occurred earlier than PeV-A3, agreeing with seroprevalence findings [10,11], but conflicting with RT-PCR-based studies [11,31]. However, the RT-PCR studies relied upon clinical samples, which may bias the PeV detection ages as PeV-A3 is associated primarily with disease before age 3 months [2,3,5,7,11].…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…PeV-A1 detections occurred earlier than PeV-A3, agreeing with seroprevalence findings [10,11], but conflicting with RT-PCR-based studies [11,31]. However, the RT-PCR studies relied upon clinical samples, which may bias the PeV detection ages as PeV-A3 is associated primarily with disease before age 3 months [2,3,5,7,11].…”
Section: Discussionmentioning
confidence: 79%
“…The overall PeV incidence rate was 144 (95%CI, 128-161) episodes per 100 child-years. Incidence rates for the 3 major types (PeV-A types 1, 3, and 6) were 64 (95% CI, 54-75), 24 (95% CI, [19][20][21][22][23][24][25][26][27][28][29][30][31][32], and 27 (95% CI, 21-35) episodes per 100 childyears, respectively. After the first 3 months of life, the incidence of new PeV infections rose steadily until age 8 months before plateauing and then gradually declining in the second year ( Supplementary Figure 4).…”
Section: Parechovirus a Infection Characteristicsmentioning
confidence: 99%
“…In the community, non‐hospitalised, confirmed cases should avoid contact with other young children (including childcare and school attendance) until symptoms have fully resolved. Contacts of confirmed cases should be made aware that older children and adults may develop mild upper respiratory or diarrhoeal symptoms 39 . There are cases of transmission from mildly symptomatic children to adults resulting in severe acute illness, but these appear to be uncommon 34 .…”
Section: Managing Parechovirus Infectionmentioning
confidence: 99%
“…The reason for this is not known and as these viruses are easily transmitted by the oral-faecal and respiratory routes 30 , it may be related to exposure and immunity within families e.g. outbreaks occurring when there is both an older sibling lacking prior HPeV3 exposure plus waning or no maternally derived HPeV3 passive immunity in the young infant 30, 34 . Studies from Japan have indicated that antibodies to HPeV3 are only present in 15% of children from 7 months to 1 year of age, but that seropositivity increases to 45% in 2–3 year old and to 85% in 4–6 year old children 11, 35 .…”
Section: Introductionmentioning
confidence: 99%